2022
DOI: 10.1021/acsomega.2c06119
|View full text |Cite
|
Sign up to set email alerts
|

Single-Ion Magnets with Giant Magnetic Anisotropy and Zero-Field Splitting

Abstract: The design of mononuclear molecular nanomagnets exhibiting a huge energy barrier to the reversal of magnetization have seen a surge of interest during the last few decades due to their potential technological applications. More specifically, singleion magnets are peculiarly attractive by virtue of their rich quantum behavior and distinct fine structure. These are viable candidates for implementation as single-molecule high-density information storage devices and other applications in future quantum technologie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 94 publications
0
9
0
Order By: Relevance
“…6. The curves fit perfectly to a Raman-like decay process with C = 10 2.8 (2) , m = 2.6(3) and C = 10 2.7 (2) , m = 2.7(4) under 1 kOe and 2 kOe external fields, respectively. Although a value of m = 9 would be expected, several examples of lower values (m E 4-5) have also been reported for Kramer ions.…”
Section: Dynamic Magnetic Measurementsmentioning
confidence: 60%
See 1 more Smart Citation
“…6. The curves fit perfectly to a Raman-like decay process with C = 10 2.8 (2) , m = 2.6(3) and C = 10 2.7 (2) , m = 2.7(4) under 1 kOe and 2 kOe external fields, respectively. Although a value of m = 9 would be expected, several examples of lower values (m E 4-5) have also been reported for Kramer ions.…”
Section: Dynamic Magnetic Measurementsmentioning
confidence: 60%
“…In subsequent years, several studies have shown that many lanthanide complexes can also show magnetization relaxation, some at much higher temperatures than those originally reported by Ishikawa. 2 For example, the dysprosium metallocene cation [Dy(Cp ttt ) 2 ] + (Cp ttt = 1,2,4tri(tert-butyl)cyclopentadienide) behaves as a single ion magnet with a magnetization reversal barrier U eff higher than 1250 cm À1 in zero field and a magnetic blocking temperature T B = 60 K, below which it exhibits hysteresis and coercivity. 3,4 Furthermore, changing Cp ttt by Cp iPr5 and Cp* (penta-isopropylcyclopentadienide and pentamethylcyclopentadienide, respectively) in [(Cp iPr5 )Dy(Cp*)] + made it possible for the first time to overcome the nitrogen boiling point barrier with T B = 80 K and U eff = 1541 cm À1 .…”
Section: Introductionmentioning
confidence: 99%
“…Describing the magnetic properties of the complex [Ni-(MDABCO) 2 Cl 3 ] +37 only within the conventional analytic techniques and approximations 11,25,38,47 turns out to be unfeasible as we have shown here. The energy spectrum of the compound obtained within these approaches is depicted in Figure 2 with the corresponding numerical representation given in the Supporting Material (Section S.5).…”
Section: Constraint Free Theorymentioning
confidence: 96%
“…The magnetic properties of transition-metal-based molecular and single-ion magnets are tightly related to the local coordination of metal ions. In general, the CF environment shaped by the bond lengths, type of ligands, coordination number, and geometric symmetry is the main precursor to a particular fine structure related to the ground state (FSG) resulting from the spin–orbit (SO) coupling. , There exists, however, an additional characteristic behind the distinct magnetic behavior among the metal ions belonging to the same row of the periodic system of elements, that is, the extent of valence subshell occupancy influencing quantitatively the effect of CF and SO coupling on the fine structure (FS) due to Pauli’s principle. In that respect, the high-spin 3d 8 coordination complexes and their ensuing polynuclear nanomagnets are of particular interest, since at a given coordination, they tend to show an unusual magnetic anisotropy (MA).…”
Section: Introductionmentioning
confidence: 99%
“…For lanthanide-based SMMs, there are also barriers for magnetization and relaxation processes. [3][4][5][6][7]11,[13][14][15][16][17][18][19][21][22][23][24][25]36 Recent advancements have contributed to the development of more efficient SMMs with improved stability and control over magnetic behavior.…”
Section: Introductionmentioning
confidence: 99%